2017
DOI: 10.21101/cejph.a4724
|View full text |Cite
|
Sign up to set email alerts
|

Body-Image Dissatisfaction and Weight-Control Behaviour in Slovak Adolescents

Abstract: Body-image dissatisfaction and weight-control behaviour are issues particularly in girls, however, they did not necessarily correspond with actual obesity. The most commonly used weight-reduction behaviours are in the same way important aspects of a healthy lifestyle. There is room to improve obesity control, particularly within primary health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…Adolescents, however, have difficulties with an adequate assessment of their body weight, and often overestimate or underestimate their body weight. Studies showed that the body weight perception depended on the age and gender of respondents [2,6,28,29]. In a representative HBSC study, conducted in Poland in 2018 among 5225 students aged 11-15 years, only half of adolescents with normal body weight were able to properly assess their body weight.…”
Section: Dissatisfaction With Body Weight and Socio-demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents, however, have difficulties with an adequate assessment of their body weight, and often overestimate or underestimate their body weight. Studies showed that the body weight perception depended on the age and gender of respondents [2,6,28,29]. In a representative HBSC study, conducted in Poland in 2018 among 5225 students aged 11-15 years, only half of adolescents with normal body weight were able to properly assess their body weight.…”
Section: Dissatisfaction With Body Weight and Socio-demographic Factorsmentioning
confidence: 99%
“…Adolescents with a higher BMI and body weight overestimation demonstrated higher body image concerns, and a poorer eating-related behavioral profile. In studies conducted in Slovakia [28] among adolescents aged 13 to 15 who assessed their body weight as too high, the most frequent weight-reduction behaviors were drinking more water, eating more fruits and vegetables, and consuming fewer sweets and soft drinks. Girls prevailed above boys in the use of these dietary methods.…”
Section: Dissatisfaction With Body Weight and Compliance With Nutritimentioning
confidence: 99%
“…In relation to sex, in this study, it was concluded that most girls were dissatisfied with excess weight. International (21)(22) and national (23)(24) studies showed that there are more cases of overestimating body image or weight in girls. A recent study performed with 2765 adolescents in Europe (21) concluded that body image dissatisfaction and weight control behavior are issues for girls in particular.…”
Section: Perception Of Body Image and Nutritional Status In Adolescenmentioning
confidence: 99%
“…International (21)(22) and national (23)(24) studies showed that there are more cases of overestimating body image or weight in girls. A recent study performed with 2765 adolescents in Europe (21) concluded that body image dissatisfaction and weight control behavior are issues for girls in particular. This difference between real and ideal silhouette with higher incidence in girls may result in a differential diagnosis of body dysmorphic disorder, since it is more prevalent in women, beginning at the age between 15 and 30 years (9) .…”
Section: Perception Of Body Image and Nutritional Status In Adolescenmentioning
confidence: 99%
“…Body dissatisfaction is a growing public health concern as it is one of the major reasons for eating disorders and fad diets among adolescents. (7 )The unrealistic image created and propagated by the mass media are also often blamed for faulty diet trends followed by adolescence. (8) The extensive use of highly visual social media (HVSM) for example, Instagram and Snap chat focusing on celebrities and peers have specified rising body image apprehensions among adolescents.…”
Section: Introductionmentioning
confidence: 99%